2020
DOI: 10.1097/md.0000000000021724
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intraductal RFA in patients with malignant biliary obstruction

Abstract: Background/Aims: Intraductal radiofrequency ablation (ID-RFA) is a novel therapy for unresectable malignant biliary obstructions. ID-RFA for perihilar lesions is associated with a high risk of adverse events. We aimed to evaluate the feasibility and efficacy of temperature-controlled ID-RFA for perihilar malignant biliary obstruction. Methods: Sixteen patients with pathologically proven perihilar cholangiocarcinoma were prospectively enrolled to evaluate the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…19 With temperature-controlled RFA system, no severe AEs have been reported including in our study. [16][17][18][19][20] Through our animal experiment, we determined a safe and effective preset for perihilar ID-RFA. With this preset, every AE of the RFA group was mild to moderate, and AE rates did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 With temperature-controlled RFA system, no severe AEs have been reported including in our study. [16][17][18][19][20] Through our animal experiment, we determined a safe and effective preset for perihilar ID-RFA. With this preset, every AE of the RFA group was mild to moderate, and AE rates did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a temperature‐controlled RFA system was newly developed to avoid this problem. To date, published data have shown no thermal injury‐related AE after a temperature‐controlled ID‐RFA in MBO 15‐19 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since this study, 14 single-arm studies have been conducted to date (Table 1). 18,[26][27][28][29][30][31][32][33][34][35][36][37][38] Figueroa-Barojas et al and Wang et al revealed that after RFA, there was a significant increase in stricture diameter, 27,32 which is considered a measure of the effectiveness of RFA in prolonging stent patency. These studies reported a mean or median stent patency period ranging from 91.5-276 days.…”
Section: Impact Of Rfa On Stent Patencymentioning
confidence: 99%
“…T HE RATE OF AE of endoscopic RFA has been reported to be 4.2-35%. 18,[26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44][45][46][47] Since the definition of AE varies between studies, it is difficult to interpret these numbers in the context of a clinical setting. However, according to five reports comparing the rates of AE between patients treated with or without RFA, no significant difference was observed.…”
Section: Adverse Events Of Endoscopic Rfamentioning
confidence: 99%